Фінансово-економічна безпека як об’єкт управління в менеджменті підприємства - Новікова, М. М. (НТУ "ХПІ", 2014)
В статті удосконалено поняття "фінансово-економічна безпека підприємства" на основі узагальнення понять "економічна безпека", "фінансова безпека", "фінансово-економічна безпека", що дає можливість спрямувати управлінський вплив на забезпечення фінансової стійкості підприємства як основи фінансово-економічної безпеки в динамічних умовах внутрішнього та зовнішнього середовища.

The complexity of modern stage of development of Ukrainian cities actualizes the problem of efficient management of this process. The complexity of the process of comprehensive management of social development of the city due to the simultaneity of management actions on the city by public authorities of the Central and regional levels, as well as local authorities. The consequence of this objective is the need to ensure comprehensiveness and consistency of these effects as one of the most important conditions for ensuring the efficient management of social development of the city.
Keywords: управлінський вплив; зовнішнє середовище; фінансовий стан; коефіцієнт автономії; коефіцієнт абсолютної ліквідності; social policy; social development city